INFLEXÃO PARA AUTONOMIA: A PERCEPÇÃO ESTRATÉGICA DA ATIVIDADE DE PESQUISA NAS UNIVERSIDADES DA REGIÃO METROPOLITANA DE SALVADOR - Gesteira, Evandro Teixeira (2013)
The study analyzes the management model of Stricto Sensu graduation programs in universities through the four phases taxonomy of research and development (R&D), as an organizational development variable. We study the concept of organizational strategic management, specifically within universities, considering the R & D as a strategic activity. Therefore, we evaluate the academic model used by universities under the legal and economic perspective, and the role played by R&D in this model, as a strategic variable for public and private universities, identifying the need for these organizations to develop strategic management under the perspective of a new organizational model of knowledge management as a competitive differential. For this purpose, a new taxonomy is established indicating that companies vary from a condition in which the research activity develops incipiently as an organizational activity, towards a condition in which it´s understood as means of promoting economic and social development